1995
DOI: 10.1200/jco.1995.13.1.210
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacologic studies of the camptothecin analog irinotecan administered every 3 weeks in cancer patients.

Abstract: The MTD of CPT-11 administered as a 30-minute IV infusion every 3 weeks is 600 mg/m2, with granulocytopenia being dose-limiting. At 350 mg/m2, diarrhea appeared dose-limiting, but high-dose loperamide reduced this toxicity and allowed dose escalation. For safety reasons, the recommended dose is presently 350 mg/m2 every 3 weeks; more experience must be gained to establish the feasibility of a higher dose in large multicentric phase II studies. However, when careful monitoring of gastrointestinal toxicities is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
77
1
8

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(96 citation statements)
references
References 21 publications
7
77
1
8
Order By: Relevance
“…Explanations may be that various nutrients in tissue culture medium might inhibit the activation of the enzyme or that the carboxylesterase extract from porcine liver is not a good substitute for the endogenous carboxylesterase converting CPT-11 in other species. Of interest, however, regardless of the dose of CPT-11 administered to patients, the proportion of SN-38 formed was low and varied between 1.3% and 5.8% (Abigerges et al, 1995). An explanation may be the complicated metabolic pathway of CPT-1 1, as at least 15 metabolites have been detected in the bile of a patient (Lokiec et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Explanations may be that various nutrients in tissue culture medium might inhibit the activation of the enzyme or that the carboxylesterase extract from porcine liver is not a good substitute for the endogenous carboxylesterase converting CPT-11 in other species. Of interest, however, regardless of the dose of CPT-11 administered to patients, the proportion of SN-38 formed was low and varied between 1.3% and 5.8% (Abigerges et al, 1995). An explanation may be the complicated metabolic pathway of CPT-1 1, as at least 15 metabolites have been detected in the bile of a patient (Lokiec et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In a phase I trial by Abigerges et al (1995), there were two recommended doses: 350 mg m À2 without highdose loperamide and 600 mg m À2 with high-dose loperamide. With the exception of one responder treated at 260 mg m À2 , all objective responses were observed at dose levels above 350 mg m À2 .…”
mentioning
confidence: 99%
“…Such a low complication rate may be explained by the low daily dose of CPT-11. In fact, a phase I study demonstrated that the gastrointestinal toxicity induced by CPT-11 increased in intensity with greater doses of the drug (Albigerges et al, 1995). Leukopenia grade 3 -4 occurred in six patients (18%).…”
Section: Toxicitymentioning
confidence: 99%
“…The administration of a third line of chemotherapy to our patients has been made possible due to the low-toxicity profile resulting from the bifractionated administration of both L-OHP in first-line chemotherapy and campthotecin in second-line chemotherapy. The lower daily dose of CPT-11 decreases the peak plasma level, thus decreasing the toxicity profile, while efficacy is not altered (Albigerges et al, 1995). In view of the palliative intents that chemotherapy accomplishes in the treatment of pretreated colorectal cancer, current approaches should be designed to find active but less toxic drug combinations.…”
Section: Months)mentioning
confidence: 99%
See 1 more Smart Citation